KINERJA PERBANKAN KONVENSIONAL DI INDONESIA - Thalia Anggiani; Ira Santika Sinaga; D. Sakuntala (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2020)
This research aims to determine the impact of Return on Assets, Operational Efficiency Ratio, Non Performing Loan and Loan to Deposit Ratio on Share prices at Conventional Banks on the Indonesia Stock Exchange in 2014 to 2018. The sampling method used was purposive sampling technique. The number of samples obtained was 27 conventional banks. The data used was secondary data. The analysis model uses multiple linear regression equations. The results show that partially Return On Assets have a significant positive effect on stock prices and Operational Efficiency Ratio has a significant negative effect on stock prices. The results show that simultaneously Return On Assets, Operational Efficiency Ratio, Non Performing Loan and Loan to Deposit Ratio have a significant effect on stock prices with a significance level of 0,000